Obesity II: Establishing causal links between chemical exposures and obesity - Heindel, Jerrold J.; Howard, Sarah; Agay-Shay, Keren; Arrebola, Juan P.; Audouze, Karine; Babin, Patrick J.; Barouki, Robert; Bansal, Amita; Blanc, Etienne; Cave, Matthew C.; Chatterjee, Saurabh; Chevalier, Nicolas; et al. (Biochemical pharmacology, 2022)
Reducing exposure to obesogens is a strategy for preventing obesity. [Display omitted] •There is an expanding global obesity pandemic.•Ubiquitous environmental chemicals called obesogens play a vital role in the obesity pandemic.•Exposure to obesogens occurs throughout the life course from before conception until death.•Development is the most sensitive time for obesogens to impact future weight gain across the lifespan and generations.•Obesogens can act via epigenetic mechanisms.•There is a need to expand understanding of the obesogen paradigm to clinicians and consumers. Obesity is a multifactorial disease with both genetic and environmental components. The prevailing view is that obesity results from an imbalance between energy intake and expenditure caused by overeating and insufficient exercise. We describe another environmental element that can alter the balance between energy intake and energy expenditure: obesogens. Obesogens are a subset of environmental chemicals that act as endocrine disruptors affecting metabolic endpoints. The obesogen hypothesis posits that exposure to endocrine disruptors and other chemicals can alter the development and function of the adipose tissue, liver, pancreas, gastrointestinal tract, and brain, thus changing the set point for control of metabolism. Obesogens can determine how much food is needed to maintain homeostasis and thereby increase the susceptibility to obesity. The most sensitive time for obesogen action is in utero and early childhood, in part via epigenetic programming that can be transmitted to future generations. This review explores the evidence supporting the obesogen hypothesis and highlights knowledge gaps that have prevented widespread acceptance as a contributor to the obesity pandemic. Critically, the obesogen hypothesis changes the narrative from curing obesity to preventing obesity.